Pendampingan Pembelajaran Al-Qur'an dalam Penguatan Karakter dan Spiritualitas Santri di Pondok Pesantren Modern Albasya - Dodi Irawan; Muhammad Wahyu Darmawan; Achmad Zakaria; Airlangga Arjuna Arya Gading; Mohammad Reksi Azhari Fansuri (Jurnal Aksi Dosen dan Mahasiswa, 2026)
This community service program aims to strengthen Qur'an learning and shape the character and spirituality of students at the Albasya Modern Islamic Boarding School. The activity was carried out using a participatory and collaborative approach through stages of coordination with the Islamic boarding school, identification of students' initial abilities, mentoring Qur'an learning in a classical and individual manner, character building through role models and habits, and continuous evaluation. The results of the activity showed an increase in the ability to read the Qur'an, especially in aspects of the accuracy of makhārij al-ḥurūf, application of tajwid laws, reading fluency, and students' self-confidence in reading the Qur'an. In addition, the program also had a positive impact on increasing discipline, responsibility, social awareness, and the formation of a stronger Qur'an learning culture in the Islamic boarding school environment. Good collaboration between the community service team, ustaz, and Islamic boarding school management supported the effectiveness of the implementation of the activity. Thus, mentoring in learning the Qur'an combined with character and spiritual development is an effective alternative in supporting the strengthening of Islamic education in Islamic boarding schools.